Impaired SIRT3 activity mediates cardiac dysfunction in endotoxemia by calpain-dependent disruption of ATP synthesis. (August 2019) - Koentges, Christoph; Cimolai, María C.; Pfeil, Katharina; Wolf, Dennis; Marchini, Timoteo; Tarkhnishvili, Aleksandre; Hoffmann, Michael M.; Odening, Katja E.; Diehl, Philipp; von zur Mühlen, Constantin; Alvarez, Silvia; Bode, Christoph; et al.
Abstract: Background: Sepsis-induced cardiomyopathy contributes to the high mortality of septic shock in critically ill patients. Since the underlying mechanisms are incompletely understood, we hypothesized that sepsis-induced impairment of sirtuin 3 (SIRT3) activity contributes to the development of septic cardiomyopathy. Methods and results: Treatment of mice with lipopolysaccharide (LPS) for 6 h resulted in myocardial NAD + depletion and increased mitochondrial protein acetylation, indicating impaired myocardial SIRT3 activity due to NAD + depletion. LPS treatment also resulted in impaired cardiac output in isolated working hearts, indicating endotoxemia-induced cardiomyopathy. Maintaining normal myocardial NAD + levels in LPS-treated mice by Poly(ADP-ribose)polymerase 1 (PARP1) deletion prevented cardiac dysfunction, whereas additional SIRT3 deficiency blunted this beneficial effect, indicating that impaired SIRT3 activity contributes to cardiac dysfunction in endotoxemia. Measurements of mitochondrial ATP synthesis suggest that LPS-induced contractile dysfunction may result from cardiac energy depletion due to impaired SIRT3 activity. Pharmacological inhibition of mitochondrial calpains using MDL28170 normalized LPS-induced cleavage of the ATP5A1 subunit of ATP synthase and normalized contractile dysfunction, suggesting that cardiac energy depletion may result from calpain-mediated cleavage of ATP5A1. These beneficial effects were completely blunted by SIRT3 deficiency. Finally, a gene set enrichment analysis of hearts of patients with septic, ischemic or dilated cardiomyopathy revealed a sepsis-specific suppression of SIRT3 deacetylation targets, including ATP5A1, indicating a functional relevance of SIRT3-dependent pathways in human sepsis. Conclusions: Impaired SIRT3 activity may mediate cardiac dysfunction in endotoxemia by facilitating calpain-mediated disruption of ATP synthesis, suggesting SIRT3 activation as a potential therapeutic strategy to treat septic cardiomyopathy.